The effect of unpredictability on the perception of breathlessness: a narrative review - Pavy, Fabien; Torta, Diana M.; von Leupoldt, Andreas (Frontiers in Rehabilitation Sciences, 2024)
Breathlessness is an aversive bodily sensation impacting millions of people worldwide. It is often highly detrimental for patients and can lead to profound distress and suffering. Notably, unpredictable breathlessness episodes are often reported as being more severe and unpleasant than predictable episodes, but the underlying reasons have not yet been firmly established in experimental studies. This review aimed to summarize the available empirical evidence about the perception of unpredictable breathlessness in the adult population. Specifically, we examined: 1) effects of unpredictable relative to predictable episodes of breathlessness on their perceived intensity and unpleasantness, 2) potentially associated neural and psychophysiological correlates, 3) potentially related factors such as state and trait negative affectivity. Nine studies were identified and integrated in this review, all of them conducted in healthy adult participants. The main finding across studies suggested that unpredictable compared to predictable, breathlessness elicits more frequently states of high fear and distress, which may contribute to amplify the perception of unpredictable breathlessness, especially its unpleasantness. Trait negative affectivity did not seem to directly affect the perception of unpredictable breathlessness. However, it seemed to reinforce state fear and anxiety, hence possible indirect modulatory pathways through these affective states. Studies investigating neural correlates of breathlessness perception and psychophysiological measures did not show clear associations with unpredictability. We discuss the implication of these results for future research and clinical applications, which necessitate further investigations, especially in clinical samples suffering from breathlessness.